Main directions for improving public health legislation in Russia - V. V. Golovko; A. I. Sakhno (Правоприменение)
The subject. A comprehensive study of Russian legislation in the field of biological safety indicates the need to update and systematize the legal framework for protecting the health of citizens and ensuring the sanitary and epidemiological well-being of the population as an important part of the mechanism of legal regulation of the national security of the Russian Federation. The purpose of the article is to confirm or refute hypothesis that there is a possibility and necessity of systematization and codification of public health legislation.The methodology. The authors analyze the practice of applying international law acts regulating the prevention of the spread of dangerous infectious diseases, the conclusions and recommendations of the WHO, the UN and other international organizations, as well as Russian public health legislation.The main results, scope of application. The current problems of Russian public health legislation are investigated, problems, prospects and main directions for its improvement are considered. The issues of theory and practice of legal regulation of public administration in conditions of emergency situations of a biological nature, topical aspects of strategic planning in the field of ensuring the epidemiological safety of regions are studied. Based on the results of a study of the current state of public health legislation, the main directions for its improvement and prospects for further development are substantiated, the position of the authors on the systematization and possible codification of sectoral legislation is presented. Conclusions. Codification of public health legislation is necessary, taking into account the new goals and objectives of the strategy for ensuring biological safety, the experience of applying domestic and international health regulations in a pandemic. This type of systematization of legal norms seems to be the most appropriate for improving the efficiency of the system for ensuring the sanitary and epidemiological welfare of the population of the Russian Federation.